A STUDY ON FAMILY BUSINESSES IN INDIA AND FINANCES- A QUALITATIVE APPROACH - Sethia, Rishabh (2008)
Family businesses are a very important organizational type as family's control majority of businesses around the world. In India, family controlled businesses account for 70 percent of total sales and net profits of the biggest 250 private sector companies. Family businesses are different from other businesses because of its unique setup and they play an important role in Indian economy.